Endothelin receptor antagonists influence cardiovascular morphology in uremic rats - Nabokow, Alexander; Amann, Kerstin; Wessels, Sabine; Münter, Klaus; Wagner, Jürgen; Ritz, Eberhard (Kidney international, 1999)
Endothelin receptor antagonists influence cardiovascular morphology in uremic rats. - Background - It is generally held that renal failure results in blood pressure (BP)-independent structural changes of the myocardium and the vasculature. The contribution, if any, of endothelin (ET) to these changes has been unknown.
Gesehen am 28.10.2021